Mengurai Kemacetan dalam Konteks Tata Ruang Perkotaan Yogyakarta - Dwinanta Nugroho; Hani Subagio; Muhamad Ridwan; Hari Rachmadi; Ajeng Tri Kadesti (Universitas Muara Bungo, 2023)
This study discusses the role of spatial planning in overcoming the increasingly worsening problem of traffic congestion in the urban area of Yogyakarta. This research explains how good spatial planning can contribute to reducing congestion, improving mobility and creating a more sustainable environment. The author explains that effective spatial planning must consider aspects such as residential location, land use patterns, transportation accessibility, and road infrastructure. The research results show that good spatial planning can optimize land use, reduce travel distances, and increase accessibility to various important facilities. In addition, this study also discusses the importance of community participation in the spatial planning process, because opinions and input from residents can help create solutions that are more appropriate to local needs and reduce resistance to change. The results of this research provide a better understanding of how wise spatial planning can help overcome traffic congestion, improve the quality of life in the Yogyakarta urban area, and support sustainable development. The policy implications drawn from this research can provide important guidance for policymakers, urban planners, and the public in joint efforts to face the challenges of congestion in other cities in the future.